The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/1756283x16644242
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal microbiome, barrier function, and immune system in inflammatory bowel disease: a tripartite pathophysiological circuit with implications for new therapeutic directions

Abstract: We discuss the tripartite pathophysiological circuit of inflammatory bowel disease (IBD), involving the intestinal microbiota, barrier function, and immune system. Dysfunction in each of these physiological components (dysbiosis, leaky gut, and inflammation) contributes in a mutually interdependent manner to IBD onset and exacerbation. Genetic and environmental risk factors lead to disruption of gut homeostasis: genetic risks predominantly affect the immune system, environmental risks predominantly affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
122
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(127 citation statements)
references
References 251 publications
1
122
0
4
Order By: Relevance
“…C ). A compromised intestinal barrier in diseases such as IBD has been shown to skew gut inflammation towards a more proinflammatory state . Analyses of colon pro‐ and anti‐inflammatory cytokine expression revealed that increased permeability in the post‐ABX, dysbiotic cohort was accompanied by a trending increase in the TNF:α/IL‐10 ratio (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…C ). A compromised intestinal barrier in diseases such as IBD has been shown to skew gut inflammation towards a more proinflammatory state . Analyses of colon pro‐ and anti‐inflammatory cytokine expression revealed that increased permeability in the post‐ABX, dysbiotic cohort was accompanied by a trending increase in the TNF:α/IL‐10 ratio (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Intestinal barrier disruption and endotoxin leakage into the blood stream are now recognized as important pathogenic events in a number of chronic diseases . Importantly, we recently identified intestinal barrier dysfunction as a key mediator of dysbiosis‐induced bone loss .…”
Section: Resultsmentioning
confidence: 99%
“…Metagenomics techniques can, in a single run, characterize the genetic material of the host and also of every pathogen present in the sample at the moment of death. Both advantages would be useful for canopic jar analysis, potentially relating organs from the same individual, thanks to genetic profiling, but also in order to screen genetic disorders and pathogens, and even more ambitiously, reconstruct whole microbial communities that live in our body, or microbiome, known to be intimately related with abdomen, neural, inflammatory and immune conditions [66][67][68][69]. Some applied examples: in a confirmation study performed by Shin et al [70] on a 17th century AD Korean Mummy diagnosed with atherosclerotic cardiovascular disease, several risk alleles related with the condition were found, indicating genetic predisposition of the disease.…”
Section: Discussionmentioning
confidence: 99%